An Analysis of College Students’ Morphological Error in Translating Recount Text from Indonesia to English Using Surface Strategy Taxonomy - Irawansyah, Irawansyah; Stefani, Inggrit; Imtinan, Hana Atikah; Jasmine, Amanda (Journal of linguistics, culture and communication, 2024)
This study aims to determine what morphological level errors appear in college students' translation of recount texts from Indonesian to English based on Dulay's theory of surface strategy taxonomy. Referring on this theory, errors are divided into omission, addition, mis-formation and mis-ordering. This study was conducted in a descriptive qualitative method. The population was the members of UKM Bahasa Universitas Islam Negeri Raden Intan Lampung with the sample used in this study were 15 members of UKM Bahasa taken with random sampling technique by sharing the Google Form link to all the population and only collected 15 participants. The data of this study were participants' translation results in translating recount text from Indonesian to English, which they sent in the Google Form link. The result of this study shows that there are 130 morphological errors made by students in translating recount text. The most common morphological error is inflectional error, which appears 37 times; the least common is pronoun error, and the auxiliary error, which appears 6 times. Meanwhile, the most common error in the surface level of taxonomy strategy is mis-formation error which appears 58 times, followed by omission error 42 times and addition error 30 times. In this study, researchers did not find any mis-ordering errors that appeared.